Removal of gentian violet in aqueous solution by activated carbon equilibrium, kinetics, and thermodynamic study - Moussa Abbas; Zahia Harrache; Mohamed Trari (Adsorption Science & Technology)
The quantitative kinetic and equilibrium adsorption parameters for chlorure de méthylrosaniline (gentian violet, crystal violet) removed by commercial activated carbon were studied by UV–visible spectroscopy.Activated carbon with a high specific surface area 1250 m 2 /g was characterized by the Brunauer, Emmett et Teller (BET) method and the zero charge point pH ( pzc) . The adsorption properties of both activated carbon with gentian violet were conducted at variable stirring speed 100–700 trs/min, adsorbent dose 1–8 g/l, solution pH 1–14, initial gentian violet concentration 5–15 mg/l, contact time 0–50 min, and temperature 299–323 K using batch mode operation to find the optimal conditions for a maximum adsorption. The adsorption mechanism of gentian violet was studied using the pseudo-first-order, pseudo-second-order, and Elovich kinetic models. The adsorption kinetics was found to follow a pseudo-second-order kinetic model with a determination coefficient (R 2 ) of 0.999. The Weber–Morris diffusion model was applied for the adsorption mechanism. The equilibrium adsorption data of gentian violet were analyzed by the Langmuir, Freundlich, Elovich, and Temkin models. The results indicate that the Langmuir model provides the best correlation ( q max  = 22.727, 32.258 mg/g at 26 and 40°C, respectively). The adsorption isotherms at different temperatures have been used for the determination of thermodynamic parameters, i.e. free energy (Δ G ° = − 2.30 to −5.34 kJ/mol), enthalpy (Δ H ° = 36.966 kJ/mol), entropy (Δ S ° = 0.131 kJ/mol K), and activation energy ( Ea ) 40.208 kJ/mol of gentian violet adsorption. The negative Δ G ° and positive Δ H ° indicate that the overall adsorption is spontaneous and endothermic in nature.